2020
DOI: 10.1111/ppa.13138
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, phylogeny and pathogenicity of Fusarium species from Sansevieria trifasciata in Malaysia

Abstract: Leaf blight is a common disease affecting Sansevieria trifasciata in many countries, including Malaysia. In the present study, Fusarium isolates were consistently recovered from the diseased leaves collected from various locations throughout the country. Based on morphology and multigene phylogenetic analysis using mitochondrial small subunit (mtSSU), intergenic spacer region (IGS) and translation elongation factor 1‐α (TEF1‐α) gene sequences, seven Fusarium species were identified, with F. oxysporum being the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…However, the latter being found only once in South Africa and seems to be extremely rare (Crous et al 2015;Talhinhas and Baroncelli 2021). In contrast, C. sansevieriae is reported from several countries worldwide (Nakamura et al 2006;Aldaoud et al 2011;Campoverde and Palmateer 2012;Palmateer et al 2012;Pérez-León et al 2013;Gautam et al 2012;Park et al 2013;Karimi et al 2017;Li et al 2020;Kee et al 2020b). So far known, the host plant range of C. sansevieriae is very narrow.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the latter being found only once in South Africa and seems to be extremely rare (Crous et al 2015;Talhinhas and Baroncelli 2021). In contrast, C. sansevieriae is reported from several countries worldwide (Nakamura et al 2006;Aldaoud et al 2011;Campoverde and Palmateer 2012;Palmateer et al 2012;Pérez-León et al 2013;Gautam et al 2012;Park et al 2013;Karimi et al 2017;Li et al 2020;Kee et al 2020b). So far known, the host plant range of C. sansevieriae is very narrow.…”
Section: Discussionmentioning
confidence: 99%
“…(Kee et al 2020a), Fusarium spp. (Kee et al 2020b) as well as Colletotrichum neosansevieriae and Stachybotrys sansevieriicola (Crous et al 2015). However, based on the number of reports, another fungal leaf spot pathogen, appears to be of greater importance: After observations of leaf spot (anthracnose) symptoms on S. trifasciata 'Laurentii' occurring since 1996 in subtropical regions of Japan, a Colletotrichum species was found as causal agent and introduced as new species, C. sansevieriae (Nakamura et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…These showed that F. oxysporum, which causes acacia seedlings to wilt, is the most similar to the F. oxysporum species complex from Elaeis sp. (F. elaeidis) (Lombard et al 2019), S. trifasciata (Kee et al 2020), V. planifolia (Koyyappurath et al 2016), C. melo (Bakar and Mohd 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Fungi of the Fusarium genus are cosmopolitan and can have a systemic distribution in plants. These species produce mycotoxins, such as fumonisin, fusaric acid, moniliformin, among others, that contaminate foods such as rice and corn, cause chronic and acute toxicity to humans and livestock, and thus generating a risk to food security (Leslie et al, 2005;O'Donnell et al, 2013, Nicollia, 2020, Qiu et al, 2020, in to being phytopathogens of Sansevieria trifasciata, which is an ornamental plant known as mother-in-law's tongue, and causing leaf scorch (Kee et al, 2020). They are also phytopathogens of the mango (Mangifera indica) and have been reported to cause malformation in the fruits and dwarf leaves in Mexico (Freeman et al, 2014).…”
Section: Molecular Identificationmentioning
confidence: 99%